Tinjauan Hukum Islam terhadap Jual Beli Pakaian Bekas - Zakaria (PT FORMOSA CENDEKIA GLOBAL, 2022)
The writing of this article seeks to describe the review of Islamic law on the sale and purchase of used clothing. The purpose of this article is to educate and advocate for readers. This type of research is qualitative legal research and normative legal research, namely what we know as library law research, namely legal articles that are carried out by researching based on materials sourced from libraries. Sources of data used by the author in this article include primary legal materials, namely applicable laws and regulations that provide descriptions of primary legal materials in the form of interpretations, general books, journals, documents and other references related to this article. From the results of this article, they are: First, buying and selling used clothes can be done with the fulfillment of the terms and conditions of buying and selling. Second, buying and selling used clothes can be done if the clothes do not cause negative effects (mudharat) for the buyer's body. Third, the practice of khiyar (choosing), in this case if the seller gets a defect at the time of buying and selling or after, before the delivery occurs, he is entitled to khiyar, but if in the transaction both parties know and are mutually willing, then there is no need for khiyar.